Using air quality monitoring to reduce second-hand smoke exposure in homes: The AFRESH feasibility study - Dobson, Ruaraidh (Tob Prev Cessat, 2017)
INTRODUCTION: Few interventions to reduce second-hand smoke in homes where children are present have been successful. A novel intervention was developed that included personal air-quality feedback. This study aimed to evaluate the feasibility and acceptability of delivering this theory-based intervention through small third-sector organisations in deprived areas within Scotland. METHODS: The setting was third-sector organisations in Scotland. Support workers used air quality monitors to give information on smoke-free homes to parents. This advice was structured around computer generated reports, co-developed with workers and target-group members. Participants received a monitor then received a report, which was discussed with a support worker. Two weeks later, the monitor was reinstalled and another report produced to evaluate success. Three participants and one support worker were interviewed afterwards to explore their experiences. RESULTS: One centre out of six that were approached agreed to deliver the intervention. Four participants took part. All participants saw a decline in average concentrations of PM(2.5) in their homes. In interviews, the participants and the support worker indicated that the intervention was acceptable and useful. The centres that declined to participate in the study cited a range of reasons, including a lack of staff time and perceived difficulties in recruiting members of the target population. CONCLUSIONS: This intervention was acceptable for the target population tested, and may help participants to create smoke-free homes, although it is not possible to generalise the results of this small study. However, the resources required for the delivery of AFRESH do not match with the resources available in third-sector organisations, despite smoke-free homes being a policy priority.